Axle gear oils: Friction, wear and tribofilm generation under boundary lubrication regime. (October 2017) - Hammami, Maroua; Rodrigues, Nuno; Fernandes, Carlos; Martins, Ramiro; Seabra, Jorge; Abbes, Mohamed Slim; Haddar, Mohamed
Abstract: The internal friction torque measurements in Cylindrical Roller Thrust Bearings (RTB) lubricated with axle gear oils under boundary film conditions were performed using an axial rolling bearing test rig generating tribofilms. The X-ray photoelectron spectroscopy (XPS) was used to characterize the tribofilms formed on the bearing rollers and raceways. After the tests, wear debris were found on the oil samples which lubricated the surface of the roller bearing raceways for that surface topography measurements and oil analysis (ferrography) were mandatory to measure and to visualize the occurring wear. The results obtained indicate that axle gear oil formulations and their additive packages have got a significant influence in controlling roller bearing friction and wear under boundary film lubrication. Abstract : Highlights: Experimental procedure for tribofilms generation. Surface roughness measurements on the roller raceway. Axle gear oil sample analysis. Surface analysis on the roller bearing raceways by XPS. Internal friction torque measurements of axle gear oils.